Canva Mind Mapping: Alternative Pembelajaran Inovatif Abad 21 - Trubus Kurniawan; Sriyanto Sriyanto (UM Purwokerto Press, 2022)
This article aims to describe the learning process and achievement through the mind mapping method. This article is a literature study that begins with: a) planning, b) observation, c) reflection. The process of writing this article resulted from various literature studies with a focus on using Canva for learning innovation. Learning using Canva for Mind Mapping activities is considered very suitable for the current condition of students. Learning in the 21st century must emphasize collaboration, critical thinking, creativity, and communication. Students must develop critical thinking and strong interpersonal communication skills to succeed in an increasingly fluid, interconnected and complex world. With so much information available online, teachers are now more facilitators of learning than the source of all knowledge. Teachers can ask questions, provide research tools and methods, and provide material and topic guides for problem solving. The use of technology in learning is absolutely controlled by a teacher to welcome change and learning in the 21st Century. The use of the Mind Mapping learning model using the Canva Application will be one solution to make learning more interesting and meaningful which in the end the learning objectives can be achieved optimally.